Mapping and bibliometric analysis of scientific publications on the use of textile materials for protection in pandemics - Paim, Ana Aline Mendes (2022)
One of the main segments of technical textiles are textile materials applied in the medical field. These are products specifically developed to meet the demands of healthcare applications. These products are commonly used in personal protective clothing for healthcare professionals and patients, in order to avoid or minimize the risks of cross-infections. During the occurrence of pandemics, there is a worldwide spread of an epidemic causing an excessive number of deaths. In December 2019 there were the first cases of Severe Acute Respiratory Syndrome, caused by a new type of coronavirus, SARS-CoV-2, beginning the Coronavirus Pandemic. In that regard and considering the role of medical textiles for personal protection, the purpose of this work was to map and investigate the main research focuses related to the use of textile materials for protection in pandemics, in the last five years. The methodology used is the ProKnow-C, following all of its steps from the selection of databases and keywords, to obtaining and bibliometric analyzing the final portfolio with 16 articles. From this portfolio, it was possible to gain a knowledge base about textiles materials applied in the medical field. Also, identify the most relevant journals and authors and understand the focus of research now that is the development of respiratory protection masks. Still as a result of the research carried out, it is possible to note that the efforts to solve problems related to personal protection in the Medicine field results in an intense synergy between Textile Engineering and Materials Science.